2021
DOI: 10.3390/antibiotics10070791
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance in Nosocomial Isolates of Gram-Negative Bacteria: Public Health Implications in the Latvian Context

Abstract: Antimicrobial Resistance (AMR) is one of the most serious threats in modern medicine which requires the constant monitoring of emerging trends amongst clinical isolates. However, very limited surveillance data is available in the Latvian context. In the present study, we conducted a retrospective analysis of microbiological data from one of the largest public multispecialty hospitals in Latvia from 2017 to 2020. AMR trends for 19 Gram-negative bacterial (GNB) genera were investigated. During the study period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…In our recent study, we described the antimicrobial resistance (AMR) rates in Gram-negative bacteria in our hospital from 2017–2020 [ 37 ]. Subsequently, in the present study, we aim to discuss and present the epidemiological surveillance data rates during the same period (2017–2020) in our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…In our recent study, we described the antimicrobial resistance (AMR) rates in Gram-negative bacteria in our hospital from 2017–2020 [ 37 ]. Subsequently, in the present study, we aim to discuss and present the epidemiological surveillance data rates during the same period (2017–2020) in our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Aminoglycosides like streptomycin and gentamycin are often used in combination with penicillin to treat severe nosocomial infections. Similar to aminoglycosides, amphenicols like chloramphenicol inhibit protein synthesis (Jain et al, 2021). In this study, we showed that extended exposure to AWME3 did not generate resistance of the K. pneumoniae strains, including standard NDM-1 carbapenemase-producing the ATCC BAA-2473 strain, along with the wild-type hypermucoviscous nosocomial isolate, strain K. pneumoniae KPi1627 and the environmental isolate, strain K. pneumoniae KPM9.…”
Section: Discussionmentioning
confidence: 68%
“…For the last few decades, the management of HAIs has played a central role to reduce the rate of infections. The need for tracking, security measures, and timely focused prevention actions has arisen due to growing rates of antimicrobial resistance [ 11 , 12 , 13 ]. Several scientific contributions have shown empirically that the participation in systems of active surveillance of HAIs relate, over time, with a reduction in the incidence of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%